2021
DOI: 10.1002/cnr2.1425
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial on acute toxicities of weekly vs three‐weekly cisplatin‐based chemoradiation in head and neck cancer

Abstract: Background: The current first-line treatment of locally advanced head and neck carcinoma (LAHNC) is concurrent chemoradiation with three-weekly cisplatin 100 mg/m 2 . However, prescribing cisplatin at this dose increases the treatment toxicity, which may compromise the treatment results. An alternative schedule is weekly 40 mg/m 2 cisplatin.Aim: To compare the acute hematologic and renal toxicities of these two regimens.Methods: This randomized clinical trial included 77 LAHNC patients who were allocated to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…13 After their report was published in mid-2000s, many reports have compared tri-weekly HDC and weekly LDC administrations directly and assessed the superiority in terms of outcomes and AEs that appeared in some journals. 4,5,14-19 Oosting et al 4 compared patients with high-risk postoperative HNSCC treated in 2 different tertiary cancer centres with different institutional practices: one centre used CRT with HDC[tri-weekly 100 mg/m 2 ] and the other used CRT with LDC [weekly 50 mg/m 2 ]. The mean cumulative cisplatin dose and the rate of cumulative cisplatin ⩾200 mg/m 2 were 239.8 mg/m 2 % and 85.2% in a centre using LDC, while those using HDC were 199.4 mg/m 2 % and 67.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 After their report was published in mid-2000s, many reports have compared tri-weekly HDC and weekly LDC administrations directly and assessed the superiority in terms of outcomes and AEs that appeared in some journals. 4,5,14-19 Oosting et al 4 compared patients with high-risk postoperative HNSCC treated in 2 different tertiary cancer centres with different institutional practices: one centre used CRT with HDC[tri-weekly 100 mg/m 2 ] and the other used CRT with LDC [weekly 50 mg/m 2 ]. The mean cumulative cisplatin dose and the rate of cumulative cisplatin ⩾200 mg/m 2 were 239.8 mg/m 2 % and 85.2% in a centre using LDC, while those using HDC were 199.4 mg/m 2 % and 67.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, HDC tended to lead to a higher rate of acute renal toxicity than LDC; 5,15,16 however, 1 paper from Iran reported that renal dysfunction was observed more in LDC group than HDC group. 14 This issue may depend on dietary habit or water intake of people of the nation.…”
Section: Discussionmentioning
confidence: 99%
“…While some have reported that mucositis (all grades qw 61.2 vs. q3w 87.6%; severe qw 12.1 vs. q3w 34%) was more common and severe with high dose cisplatin [25]. In contrast, no differences in either incidence or intensity of mucositis have been reported in other trials in which the tumor impact of the two regimens was evaluated for both oral/oropharyngeal cancers [26][27][28]. The results of a recently reported Phase 2 interventional trial in which trained evaluators scored mucositis throughout treatment agrees with that conclusion [8].…”
Section: Concomitant Chemotherapymentioning
confidence: 99%
“…There may be some tendency to show higher severe myelosuppression rate in triweekly cisplatin treated group. However, most reports demonstrated only the rate of severe myelosuppression and median/mean age of participants [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], which made it difficult to clearly evaluate the effects of triweekly/weekly cisplatin for older patients ( Table 2 ). It seems that the use of chemotherapy for the elderly will increase more and more in near future.…”
Section: Cisplatin-associated Toxicitiesmentioning
confidence: 99%